2006
DOI: 10.1177/0017896906069378
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the relationship between socio-economic position and physical activity

Abstract: Objective The aim of the present review was to examine epidemiological evidence to determine if there is strong evidence of a positive gradient of increasing physical activity across the socio-economic strata, and how relationships are affected by socio-economic measurement. Design Systematic review. Method A search of major databases was conducted to identify published studies that reported physical activity in relation to socio-economic position (SEP) in adults. Results Twenty-eight cross-sectional and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
317
4
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(361 citation statements)
references
References 68 publications
(293 reference statements)
25
317
4
15
Order By: Relevance
“…In any case, however, the original result that richer individuals are, ceteris paribus, less overweight is preserved. In line with the empirical observation the extended model predicts that richer people, on average, exercise more for weight loss (Gidlow et al, 2006).…”
Section: Feeling Fatsupporting
confidence: 79%
“…In any case, however, the original result that richer individuals are, ceteris paribus, less overweight is preserved. In line with the empirical observation the extended model predicts that richer people, on average, exercise more for weight loss (Gidlow et al, 2006).…”
Section: Feeling Fatsupporting
confidence: 79%
“…Possible explanations for the influence of the lower socioeconomic level on health conditions of the population fall on their lack of access to the health system, beyond the lower degree of information and understanding of the disease and their determinants (24) . In addition, studies have already shown the negative impact the lower socioeconomic level exerts on physical activity and adoption of a healthy diet (25) . In the present study, the socioeconomic variable was represented by the source of funding of patient surgery, dichotomized into the SUS and non-SUS groups, but association between this variable and arterial hypertension was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Studies have also shown that physical inactivity and poor nutrition are disproportionately experienced by those experiencing socioeconomic disadvantage. [14][15][16][17][18] Efforts to reduce the high prevalence of overweight and obesity among women with children who are socioeconomically disadvantaged are currently hindered by a lack of understanding of the aetiology of weight gain and obesity in this group. Although diets high in energy and fat and sedentary lifestyles are believed to be key behaviours in the aetiology of overweight and obesity among young women generally, 3,9,10 the relative contributions of these factors to weight gain in women with children, particularly those whose risk may be increased because of living in socioeconomically disadvantage neighbourhoods, are not well understood.…”
Section: Introductionmentioning
confidence: 99%